Behind of the criticality for rare earth elements: Surplus of China's yttrium. (June 2022) - Xiao, Shijiang; Geng, Yong; Rui, Xue; Su, Chang; Yao, Tianli
Abstract: Yttrium (Y), mainly using for phosphors, is considered as one of critical rare earth elements (REEs) in several countries. However, its flows and stocks in the whole life and fundamental supply and demand are still unclear, leading to that it is difficult to measure its criticality. This study aims to estimate China's Y flows and stocks for the period of 2000–2019 by applying dynamic material flow analysis. The results indicate that: (1) 146 kilo tons (kt) Y concentrates were flowed into anthropogenic system, and 33 kt Y were used in fluorescent lights, accounting for 80% of the total final use; (2) Y supply had been imbalanced with its demand, generating 39 kt Y surplus during the study period; (3) accumulative net Y export was 55 kt, in which primary products and final products accounted for 84% of the total export. Finally, three policy implications are proposed, including dynamic and specific list of individual critical REE, emergent Y recycling plans, and comprehensive stockpile policies. Highlights: Almost 5 kilo tons of yttrium became in-use stock and 17 kilo tons of yttrium were disposed of. Imbalanced supply and demand lead to 39 kilo tons of yttrium surplus over the past two decades. Primary products and final products are dominant export products, accounting for 85% of the total export. Comprehensive stockpile policies are able to achieve conservation of yttrium surplus in China.